2004
DOI: 10.1182/blood-2003-11-3884
|View full text |Cite
|
Sign up to set email alerts
|

The etiology of severe anemia in a village and a periurban area in Mali

Abstract: Severe anemia is one of the major complications of malaria in Africa. We studied 2 populations, one in a village and the second in a periurban area in Mali, to understand the preventable factors in the disease. The 2 correlates of disease were parasitemia above 100 000 parasitized red blood cells per microliter (0.1 ؋ 10 12 /L) and a low baseline hemoglobin level. All cases of moderate to severe anemia occurred in children under 3.2 years of age. Raising the baseline hemoglobin level and lowering peak parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 12 publications
3
37
1
Order By: Relevance
“…Mortality is greatest when anaemia is severe (Hb < 50 g/l), and complicated by other signs of severity [ 40]. Two factors correlate best with the development of severe anaemia: haemoglobin concentration preceding the malaria transmission season, and the parasite density achieved during incident infections [ 41]. We found no evidence for an effect of α + -thalassaemia on either of these parameters.…”
Section: Discussionmentioning
confidence: 78%
“…Mortality is greatest when anaemia is severe (Hb < 50 g/l), and complicated by other signs of severity [ 40]. Two factors correlate best with the development of severe anaemia: haemoglobin concentration preceding the malaria transmission season, and the parasite density achieved during incident infections [ 41]. We found no evidence for an effect of α + -thalassaemia on either of these parameters.…”
Section: Discussionmentioning
confidence: 78%
“…We found that Ab levels to Pf proteins rose dramatically in children during the 6-month malaria season; however, most of this response appeared to be short-lived based on cross-sectional analysis at the end of the 6-month dry season, which revealed only modest incremental increases in Ab levels with age. Because there is little to no Pf transmission at the study site during the 6-month dry season (12,13) and IgG has a half-life of ∼21 days (48), we infer that Pf-specific Abs in circulation at the end of the dry season are generated by long-lived plasma cells (LLPCs), whereas the increase in Ab levels observed after the malaria season likely reflects the differentiation of naive and/or memory B cells (MBCs) into short-lived plasma cells (SLPCs) that disappear by the end of the next dry season. Thus, it appears that the Pf-specific LLPC compartment gradually "fills" with repeated Pf exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to a single causative agent or factor or an interaction among several causative agents or factors. In most cases, it is due to two or more causative agents rather than a single one [1][2][3] . Malaria, bacteraemia, helminthiasis, human parvovirus B19 (B19V) infection and other infections such as tuberculosis and HIV/AIDS have been widely reported as important factors contributing to the high prevalence of anaemia in many populations [3][4][5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%